Neonatal severe hyperparathyroidism: a case report - Mahmood Shaukat; Hafiz Mahmood Ahmad; Muhammad Umar Shafiq (Journal of the Pakistan Medical Association, 2022)
Neonatal severe hyperparathyroidism (NSHPT) is a rare genetic disorder that presents within the first six months of life. We present the case report of a male child who presented to us in the first month of his life with symptoms of lethargy, constipation, and reluctance to feed. One sibling of the child had died earlier with similar symptoms in the first six months of life. Upon physical examination, the child was lethargic, dehydrated, had bradycardia with hyperreflexia. Serum electrolyte analysis showed hypercalcaemia and hypophosphataemia. Further workup revealed elevated serum parathyroid hormone levels and Calcium sensing receptor (CaSR) gene mutation in autosomal recessive patterns. The father was discovered to be heterozygous for the same mutation but is asymptomatic. Diagnosis of neonatal severe hyperparathyroidism was made and the child was managed medically with intravenous fluids, Furosemide, Pamidronate, and Cinacalcet. ---Continue